The role of trade and investment policies in the implementation of the Monterrey Consensus : regional perspectives 2026-02-16T00:47:17+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... (ESCAP studies in trade and investment ;, 2005)

(untitled)
"Papers and comments presented at the Expert Group Meeting on the Role of Trade and Investment Policies in the Implementation of the Monterrey Consensus : Bangkok, 26-27 October 2004."